Upaya Meningkatkan Kreativitas Anak Usia Dini Melalui Bermain Plastisin: - Ika Awaliyah; Zaenal Abidin; Rusdiono Mukri (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
Creativity is the ability to think about things in new and unusual ways and give birth to something unique, or create something original. Plasticine is a material that is made of flexible and can be shaped as desired. This study aims to increase early childhood creativity through playing plasticine. This type of research is Classroom Action Research. This research was conducted in 2 cycles, each stage, namely Planning, Implementation, Observation and Reflection. Data collection techniques are observation, interviews, documentation, field notes. The data analysis used is descriptive analysis with a qualitative approach. Subjects in this study were group B with a total of 14 children consisting of 9 boys and 5 girls. The results showed that the creativity of children increased, namely from the pre-cycle the number of undeveloped children decreased from 12 children to 0 (85.7%) in cycles I and II, then children who began to develop from pre-cycle 2 children (14 , 3%) to 9 children (64.3%) in cycle I and to 0 in cycle II. Children who developed as expected from pre-cycle from none to 5 children (35.7%) in cycle I and 3 children (21.4%) in cycle 2. Children who developed very well in pre-cycle and cycle I did not there were 11 children (78.65%). These results indicate that playing plasticine can increase the creativity of early childhood in RA Ibnu Sina, Pamijahan District, Bogor Regency.